G-C3N4 / Bi / BiPO4 photocatalyst as well as preparation method and application thereof

By introducing Bi electron intermediary into the g-C3N4/BiPO4 photocatalyst, the g-C3N4/Bi/BiPO4 ternary composite photocatalyst is solved, and the existing photocatalysts are difficult to remove tetracycline in depth is achieved, and efficient degradation of tetracycline under visible light is achieved.

CN119771471APending Publication Date: 2025-04-08ZHONGBEI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510024186.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The existing g-C3N4 and BiPO4 photocatalysts are difficult to achieve deep removal of organic pollutants such as tetracycline when using visible light.

Method used

By introducing Bi electron intermediary on the basis of g-C3N4/BiPO4, a ternary composite photocatalyst was formed, and a hydrothermal method and thermal polymerization method was prepared, and Bi atoms were reduced in situ by potassium borohydride wet reduction method.

Benefits of technology

Complete removal of tetracycline under visible light irradiation was achieved, the degradation rate reached 100% for 60 minutes of reaction, and a significant degradation effect was shown at the initial pH of 11.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119771471A_ABST
    Figure CN119771471A_ABST
Patent Text Reader

Abstract

The invention provides a g-C3N4 / Bi / BiPO4 photocatalyst as well as a preparation method and application of the g-C3N4 / Bi / BiPO4 photocatalyst. The g-C3N4 / BiPO4 composite photocatalyst is prepared by combining a hydrothermal method and a thermal polymerization method, Bi elementary substances are reduced in situ through a potassium borohydride wet reduction method, and the g-C3N4 / Bi / BiPO4 ternary composite photocatalyst is formed. Compared with single g-C3N4, BiPO4 and binary g-C3N4 / BiPO4, the ternary g-C3N4 / Bi / BiPO4 catalyst has the advantages that the deep removal of tetracycline can be realized; and when the initial pH value is 11, the degradation rate after the reaction for 60 minutes can reach 100%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of photocatalysis, and in particular to a g-C3N4 / Bi / BiPO4 photocatalyst and a preparation method and application thereof. Background Art

[0002] With the rapid development of modern industry and the improvement of people's living standards, organic pollutants such as antibiotics are discharged into water bodies, causing increasingly serious water pollution. Graphite phase carbon nitride (g-C3N4) has abundant raw materials on earth, simple preparation methods, high chemical and thermal stability, visible light response and easy structural regulation. In recent years, it has been considered as one of the most successful π-conjugated polymers; however, the single g-C3N4 catalyst has the problem of easy recombination of photogenerated hole-electron pairs. Studies have shown that various methods such as doping modification, heterojunction construction, and synthesis of monolayer or porous structured g-C3N4 are beneficial to enhance the directional migration and utilization of space charges to varying degrees, thereby improving its photocatalytic degradation efficiency. As a typical non-transition metal phosphate and a typical p-type semiconductor, bismuth phosphate (BiPO4) exhibits excellent photocatalytic performance due to its high crystallinity, good stability and phosphoric acid-induced intrinsic redox activity; however, due to the wide band gap, BiPO4 can only use ultraviolet light, and the photogenerated charge separation efficiency of a single BiPO4 photocatalyst is not high enough.

[0003] The Z-type heterojunction catalyst developed based on the electron transfer mechanism in natural photosynthesis can achieve the goal of accelerating carrier separation and electron transfer, while retaining the catalyst's high electron reduction potential and high hole oxidation potential, so that the reaction system produces more active free radicals. g-C3N4 / BiPO4 belongs to the Z-type heterojunction photocatalyst, which can absorb ultraviolet light and visible light at the same time; compared with single g-C3N4 and BiPO4 catalysts, g-C3N4 / BiPO4 can generate more positive potential photogenerated holes and more negative potential photogenerated electrons while enhancing their respective photogenerated charge separation capabilities, effectively improving the photocatalytic degradation ability; however, g-C3N4 / BiPO4 still fails to achieve deep photocatalytic removal of organic pollutants such as tetracycline.

[0004] In view of this, it is necessary to provide a g-C3N4 / Bi / BiPO4 photocatalyst and its preparation method and application to solve or at least alleviate the technical problems of how to obtain a photocatalyst for deep removal of organic pollutants and how to achieve deep removal of organic pollutants. Summary of the invention

[0005] The main purpose of the present invention is to provide a g-C3N4 / Bi / BiPO4 photocatalyst and its preparation method and application, aiming to solve the technical problems of how to obtain a photocatalyst for deep removal of organic pollutants and how to achieve deep removal of organic pollutants.

[0006] To achieve the above object, the present invention provides a method for preparing a g-C3N4 / Bi / BiPO4 photocatalyst, comprising the steps of:

[0007] S1, obtain BiPO4 nanocubes;

[0008] S2, obtaining a g-C3N4 / BiPO4 product based on the BiPO4 nanocubes;

[0009] S3, obtaining a g-C3N4 / Bi / BiPO4 photocatalyst based on the g-C3N4 / BiPO4 product;

[0010] The process of obtaining the g-C3N4 / Bi / BiPO4 photocatalyst based on the g-C3N4 / BiPO4 product comprises the following sub-steps:

[0011] S31, mixing polyvinyl pyrrolidone and the g-C3N4 / BiPO4 product in water to obtain a fourth treatment liquid; the mass ratio of the polyvinyl pyrrolidone to the g-C3N4 / BiPO4 product is 0.8-1.2:0.8-1.2;

[0012] S32, adding a potassium borohydride solution dropwise to the fourth treatment liquid and mixing the mixture to obtain a fifth treatment liquid; the mass volume ratio of the g-C3N4 / BiPO4 product to the potassium borohydride solution is 1 g: 50-70 mL, and the concentration of the potassium borohydride solution is 30-70 mmol / L;

[0013] S33, aging the fifth treatment liquid to obtain a sixth treatment liquid;

[0014] S34, performing solid-liquid separation on the sixth treated liquid to obtain the g-C3N4 / Bi / BiPO4 photocatalyst.

[0015] Furthermore, the process of obtaining the BiPO4 nanocubes comprises the following sub-steps:

[0016] S11, mixing ethylenediaminetetraacetic acid and bismuth nitrate in water, and adding nitric acid during the mixing process to obtain a first treatment solution; the molar ratio of the ethylenediaminetetraacetic acid to the bismuth nitrate is 0.8-1.2:0.8-1.2; the amount of the nitric acid added is based on the transparency of the solution;

[0017] S12, mixing the first treatment liquid and dipotassium hydrogen phosphate to obtain a second treatment liquid; the molar ratio of the dipotassium hydrogen phosphate to the bismuth nitrate is 0.8-1.2:0.8-1.2;

[0018] S13, subjecting the second treatment liquid to a hydrothermal treatment to obtain a reaction liquid; the temperature of the hydrothermal treatment is 160-200° C., and the duration of the hydrothermal treatment is 8-15 hours;

[0019] S14, performing solid-liquid separation on the reaction solution to obtain BiPO4 nanocubes.

[0020] Further, in the sub-step S11, the ratio of bismuth nitrate to water is 5 mmol: 50-100 mL;

[0021] In the sub-step S14, during the solid-liquid separation, the solid separation is washed, and after the solid-liquid separation, the solid separation is dried at 60-80° C. for 8-15 hours.

[0022] Furthermore, the process of obtaining the g-C3N4 / BiPO4 product based on the BiPO4 nanocubes comprises the following sub-steps:

[0023] S21, mixing melamine and the BiPO4 nanocubes in ethanol to obtain a third treatment liquid; the mass ratio of the melamine to the BiPO4 nanocubes is 10-30:1;

[0024] S22, drying the third treatment liquid to obtain a dried product;

[0025] S23, subjecting the dried material to thermal polymerization treatment, and obtaining the g-C3N4 / BiPO4 product after cooling; the temperature of the thermal polymerization treatment is 500-600°C, and the insulation time of the thermal polymerization treatment is 1.5-3h.

[0026] Further, in the sub-step S21, the mass volume ratio of the melamine to the ethanol is 1-5 g: 20 mL;

[0027] In the sub-step S22, the temperature of the drying process is 70-90°C, and the duration of the drying process is 5-8h;

[0028] In the sub-step S23, the heating rate during the thermal polymerization treatment is 3-10°C / min.

[0029] Furthermore, in the sub-step S31, the mass volume ratio of the g-C3N4 / BiPO4 product and water is 0.1-1g:50mL.

[0030] Furthermore, in the sub-step S32, the potassium borohydride solution is added dropwise to the fourth treatment liquid for mixing, and after the addition is completed, the mixing is continued for 20-40 minutes;

[0031] In the sub-step S33, the aging time is 20-40 minutes.

[0032] In the sub-step S34, during the solid-liquid separation, the solid separated product is washed, and after the solid-liquid separation, the solid separated product is dried at 30-50°C.

[0033] The present invention also provides a g-C3N4 / Bi / BiPO4 photocatalyst, which is prepared by any of the preparation methods described above.

[0034] The present invention also provides a use of any of the g-C3N4 / Bi / BiPO4 photocatalysts described above in photocatalytic degradation of organic pollutants.

[0035] Furthermore, the organic pollutants include tetracycline.

[0036] Compared with the prior art, the present invention has at least the following advantages:

[0037] The present invention prepares a novel Z system g-C3N4 / Bi / BiPO4 ternary composite photocatalyst. The present invention adds Bi electronic mediator to g-C3N4 / BiPO4, improves the photogenerated charge transfer ability, and can achieve complete removal of tetracycline under the irradiation of visible light. Specifically, the present invention combines hydrothermal method with thermal polymerization method to prepare g-C3N4 / BiPO4 composite photocatalyst, and in situ reduces Bi element by potassium borohydride wet reduction method to form g-C3N4 / Bi / BiPO4 ternary composite photocatalyst. Compared with single g-C3N4, BiPO4 and binary g-C3N4 / BiPO4, the ternary g-C3N4 / Bi / BiPO4 catalyst can achieve deep photocatalytic decomposition of tetracycline, and when the initial pH is 11, the degradation rate of 60 minutes of reaction can reach 100%; and compared with other comparative materials listed in the comparative examples of the present invention, it has more application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.

[0039] Figure 1 It is a schematic diagram of the process of preparing g-C3N4 / Bi / BiPO4 photocatalyst in the present invention;

[0040] Figure 2 SEM images of g-C3N4, BiPO4, g-C3N4 / BiPO4, and g-C3N4 / Bi / BiPO4 in the present invention; (a) is the g-C3N4 in Comparative Example 1, (b) is the BiPO4 in Comparative Example 2, (c) is the g-C3N4 / BiPO4 in Example 1, and (d) is the g-C3N4 / Bi / BiPO4 in Example 1;

[0041] Figure 3 TEM image of g-C3N4 / Bi / BiPO4 in Example 1 of the present invention, with a scale of 5 nm;

[0042] Figure 4 XRD diagrams of g-C3N4 in Comparative Example 1 of the present invention, BiPO4 in Comparative Example 2, and g-C3N4 / BiPO4 and g-C3N4 / Bi / BiPO4 in Example 1;

[0043] Figure 5 It is the ultraviolet visible diffuse reflectance spectra (UV-vis DRS) of g-C3N4 in comparative example 1 of the present invention, BiPO4 in comparative example 2, and g-C3N4 / BiPO4 and g-C3N4 / Bi / BiPO4 in embodiment 1;

[0044] Figure 6 The concentration change curve of tetracycline degradation under different catalyst types in the analysis example 1 of the present invention;

[0045] Figure 7 The degradation rate curve of tetracycline under different catalyst types in the analysis example 1 of the present invention;

[0046] Figure 8 The concentration change curve of degraded tetracycline under different catalyst dosages in the analysis example 2 of the present invention;

[0047] Fig. 9 The degradation rate curve of tetracycline at different catalyst dosages in the analysis example 2 of the present invention;

[0048] Fig.10 The concentration change curve of degraded tetracycline under different initial tetracycline concentrations in the analysis example 3 of the present invention;

[0049] Fig.11 The degradation rate curve of tetracycline at different initial tetracycline concentrations in the analysis example 3 of the present invention;

[0050] Fig.12The concentration change curve of degraded tetracycline at different initial pH values ​​in the analysis example 4 of the present invention;

[0051] Fig.13 This is the rate curve of tetracycline degradation at different initial pH values ​​in Analysis Example 4 of the present invention.

[0052] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with the implementation methods and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0053] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0054] Furthermore, the technical solutions between the various embodiments of the present invention may be combined with each other, but this must be based on the fact that they can be implemented by ordinary technicians in the field. When the combination of technical solutions is mutually contradictory or cannot be implemented, it should be deemed that such combination of technical solutions does not exist and is not within the scope of protection required by the present invention.

[0055] When the embodiments give a numerical range, it should be understood that, unless otherwise specified in the present invention, the two endpoints of each numerical range and any value between the two endpoints can be selected. Unless otherwise defined, all technical and scientific terms used in the present invention and the technical personnel in this field of technology master the prior art and the record of the present invention, and any method, equipment and material of the prior art similar or equivalent to the method, equipment and material in the embodiments of the present invention can also be used to implement the present invention. In the present invention, the naming of the comparative samples in Comparative Examples 4-8 is only convenient for distinguishing them, and the specific technical features are subject to the preparation process and the synthesis process; in the present invention, the atmosphere is not controlled during the thermal polymerization and heat treatment, and it is directly exposed to the air.

[0056] See also Figure 1 It is understood that the present invention provides a method for preparing a g-C3N4 / Bi / BiPO4 photocatalyst, comprising the steps of:

[0057] S1, obtain BiPO4 nanocubes.

[0058] In the present invention, the process of obtaining the BiPO4 nanocubes includes the following sub-steps:

[0059] S11, mixing ethylenediaminetetraacetic acid and bismuth nitrate in water, and adding nitric acid during the mixing process to obtain a first treatment liquid; the nitric acid can be added dropwise; specifically, the ethylenediaminetetraacetic acid and the bismuth nitrate are first added to water under stirring, and then the nitric acid is added dropwise under stirring.

[0060] In the sub-step S11, the molar ratio of the ethylenediaminetetraacetic acid to the bismuth nitrate is 0.8-1.2:0.8-1.2; the ratio of the bismuth nitrate to water is 5mmol:50-100mL; the amount of nitric acid added is based on the transparency of the solution, that is, the transparency of the first treatment solution is used as the standard; specifically, the nitric acid exists in the form of a nitric acid solution, the mass fraction of the nitric acid in the nitric acid solution is 60-70%, and the volume ratio of the nitric acid solution to water is 1:40-50.

[0061] S12, mixing the first treatment liquid and dipotassium hydrogen phosphate to obtain a second treatment liquid; the molar ratio of the dipotassium hydrogen phosphate to the bismuth nitrate is 0.8-1.2:0.8-1.2.

[0062] S13, subjecting the second treatment liquid to hydrothermal treatment (hydrothermal reaction) to obtain a reaction liquid; the hydrothermal treatment is carried out in a hydrothermal reaction vessel; the temperature of the hydrothermal treatment is 160-200°C, and the duration of the hydrothermal treatment is 8-15h.

[0063] S14, performing solid-liquid separation on the reaction solution to obtain BiPO4 nanocubes.

[0064] In the sub-step S14, during the solid-liquid separation, the solid separation is washed (using ethanol and high-purity water), and after the solid-liquid separation, the solid separation is dried at 60-80° C. for 8-15 hours.

[0065] S2, obtaining a g-C3N4 / BiPO4 product based on the BiPO4 nanocube; the BiPO4 nanocube is obtained by using the above step S1, specifically, the BiPO4 nanocube is obtained by using the first step in Example 1.

[0066] In the present invention, the process of obtaining the g-C3N4 / BiPO4 product based on the BiPO4 nanocubes includes the following sub-steps:

[0067] S21, mixing (stirring and ultrasonically dispersing uniformly) melamine and the BiPO4 nanocubes in ethanol (volume concentration not less than 99%) to obtain a third treatment liquid; the mass ratio of the melamine and the BiPO4 nanocubes is 10-30:1; the mass volume ratio of the melamine and the ethanol is 1-5g:20mL.

[0068] S22, drying the third treatment liquid to obtain a dried product; the drying temperature is 70-90°C, and the drying time is 5-8h.

[0069] S23, subjecting the dried material to thermal polymerization treatment, and obtaining the g-C3N4 / BiPO4 product after cooling; the temperature of the thermal polymerization treatment is 500-600°C, and the insulation time of the thermal polymerization treatment is 1.5-3h; the heating rate during the thermal polymerization treatment is 3-10°C / min; the thermal polymerization treatment is carried out in a muffle furnace.

[0070] S3, obtaining a g-C3N4 / Bi / BiPO4 photocatalyst based on the g-C3N4 / BiPO4 product; the g-C3N4 / BiPO4 product is obtained by using the above steps S1 and S2, specifically, the g-C3N4 / BiPO4 product is obtained by using the first and second steps in Example 1.

[0071] In the present invention, the process of obtaining the g-C3N4 / Bi / BiPO4 photocatalyst based on the g-C3N4 / BiPO4 product includes the following sub-steps:

[0072] S31, mix polyvinyl pyrrolidone and the g-C3N4 / BiPO4 product in water, the mixing time can be 10-30 minutes, and obtain a fourth treatment liquid; the mass ratio of the polyvinyl pyrrolidone and the g-C3N4 / BiPO4 product is 0.8-1.2:0.8-1.2; the mass volume ratio of the g-C3N4 / BiPO4 product and water is 0.1-1:50mL.

[0073] S32, adding potassium borohydride solution to the fourth treatment liquid and mixing to obtain a fifth treatment liquid; the mass volume ratio of the g-C3N4 / BiPO4 product and the potassium borohydride solution is 1g:50-70mL, and the concentration of the potassium borohydride solution is 30-70mmol / L or 40-60mmol / L.

[0074] In the sub-step S32, the process of adding the potassium borohydride solution to the fourth treatment liquid and mixing the mixture includes: mixing the mixture during the process of adding the potassium borohydride solution to the fourth treatment liquid, and continuing to mix the mixture for 20-40 minutes after the addition is completed.

[0075] S33, aging the fifth treatment liquid to obtain a sixth treatment liquid; the aging time is 20-40 minutes.

[0076] S34, performing solid-liquid separation on the sixth treated liquid to obtain the g-C3N4 / Bi / BiPO4 photocatalyst.

[0077] In the sub-step S34, during the solid-liquid separation, the solid separated material is washed (with water and ethanol), and after the solid-liquid separation, the solid separated material is dried at 30-50°C.

[0078] Metal Bi has the advantages of low cost, easy access, small energy band overlap energy, high carrier mobility, etc., and can be used as an electron medium in a Z-type heterojunction; in addition, Bi has the same surface plasmon resonance (SPR) characteristics as precious metals, and can be excited by light to generate electrons; therefore, the Bi atoms obtained by in-situ reduction in the photocatalyst can simultaneously play the role of electron donor and electron mediator. In order to enhance the electron transfer ability between the heterojunction interfaces of g-C3N4 / BiPO4, the present invention uses potassium borohydride reducing agent to perform in-situ wet reduction on the basis of g-C3N4 / BiPO4 to obtain a g-C3N4 / Bi / BiPO4 ternary composite photocatalyst; wherein, the Z-type heterojunction can make the photocatalyst have a wide range of light absorption, high charge separation efficiency and strong redox ability, and the Bi atoms play the role of electron donor and electron mediator, accelerating the electron transfer effect, and its catalytic degradation of tetracycline is significant.

[0079] The present invention also provides a g-C3N4 / Bi / BiPO4 photocatalyst, which is prepared by any of the preparation methods described above.

[0080] The present invention also provides a use of any of the g-C3N4 / Bi / BiPO4 photocatalysts described above in photocatalytic degradation of organic pollutants; the organic pollutants include or are tetracycline.

[0081] The application includes: mixing the g-C3N4 / Bi / BiPO4 photocatalyst and organic waste liquid to obtain a catalytic liquid; placing the catalytic liquid under dark conditions, irradiating visible light after reaching adsorption-desorption equilibrium, and then performing solid-liquid separation to obtain a purified liquid; the time for the catalytic liquid to be in the dark condition can be 20-60 minutes or 20-40 minutes; the visible light can be provided by a xenon lamp, the power can be 300-400W, and the irradiation time of the visible light can be not less than 60 minutes or not less than 80 minutes or not less than 90 minutes, such as 80-100 minutes or 90-100 minutes.

[0082] In the present invention, the organic waste liquid contains the organic pollutants; in the organic waste liquid, the concentration of the organic pollutants is 10-40 mg / L or 10-30 mg / L or 10-20 mg / L or not more than 20 mg / L, the mass volume ratio of the g-C3N4 / Bi / BiPO4 photocatalyst and the organic waste liquid is 10-30 mg:50 mL or 10-20 mg:50 mL or 20-30 mg:50 mL; the pH of the organic waste liquid can be 7-11, specifically 11.

[0083] In the present invention, the main medicines and equipment information are as follows:

[0084] Table 1 Drug information

[0085]

[0086] Table 2 Instrument and equipment information

[0087]

[0088] The following are specific examples of the present invention:

[0089] Comparative Example 1

[0090] Melamine was placed in a muffle furnace and heated to 550°C at a rate of 5°C / min for 2 hours, then naturally cooled to room temperature. The obtained product was recorded as g-C3N4 and used for subsequent photocatalytic experiments.

[0091] In this comparative example, the SEM analysis of g-C3N4 is shown in Figure 2 As shown, it can be seen that g-C3N4 exhibits an obvious nanosheet layered structure.

[0092] In this comparative example, the XRD analysis of g-C3N4 is shown in Figure 4 As shown, it can be seen that there are two characteristic peaks attributed to g-C3N4, namely the (002) characteristic peak of conjugated aromatic ring stacking at 27.5° and the (100) characteristic peak of in-plane repeating triazine units at 13.3°.

[0093] In this comparative example, the UV-visible diffuse reflectance spectrum (UV-vis DRS) of g-C3N4 is shown in Figure 5 shown.

[0094] Example 1

[0095] Preparation of catalyst:

[0096] Step 1, preparation of BiPO4 nanocubes:

[0097] Add 5mmol EDTA (ethylenediaminetetraacetic acid) and 5mmol Bi(NO3)3·5H2O to 80mL ultrapure water; under continuous stirring, add 1.8mL concentrated nitric acid (the mass fraction of concentrated nitric acid is 68%) dropwise until the solution is transparent to obtain a first treatment liquid; add 5mmol K2HPO4·3H2O to the first treatment liquid, continue stirring to make the mixture uniform, and obtain a second treatment liquid; put the second treatment liquid into a Teflon-lined stainless steel hydrothermal reaction axe, and heat it in an oven at 180°C for 12h to obtain a reaction liquid; separate the solid separator in the reaction liquid and wash it several times with ethanol and high-purity water; then, dry the solid separator in an oven at 70°C for 12h, and the obtained sample is BiPO4 nanocube.

[0098] Step 2: Preparation of g-C3N4 / BiPO4 composite catalyst:

[0099] Add 3g of melamine and 150mg of the above-mentioned BiPO4 nanocubes into 20mL of ethanol (analytical grade, 99.5%), stir and disperse evenly by ultrasound to obtain a third treatment liquid; put the third treatment liquid into a crucible, and dry it in an oven at 80°C for 6h to obtain a dried product; put the dried product into a muffle furnace, heat it to 550°C at a rate of 5°C / min, thermally polymerize it for 2h, and then naturally cool it to room temperature. The obtained product is recorded as g-C3N4 / BiPO4 product.

[0100] The third step is to synthesize the photocatalyst containing Bi metal electron mediator (g-C3N4 / Bi / BiPO4):

[0101] 0.5 g of the above g-C3N4 / BiPO4 product and 0.5 g of PVP (polyvinyl pyrrolidone) were added to 50 mL of deionized water, and magnetic stirring was carried out for 20 min to obtain a fourth treatment liquid; potassium borohydride solution (50 mmol / L, 30 mL) was dropped into the fourth treatment liquid and stirred for 30 min to obtain a fifth treatment liquid; the fifth treatment liquid was aged (standing at room temperature) for 30 min to obtain a sixth treatment liquid; the solid separator in the sixth treatment liquid was separated and washed with water and ethanol, and then dried at 40°C to obtain a g-C3N4 / Bi / BiPO4 photocatalyst for subsequent photocatalytic experiments.

[0102] In this example, the SEM analysis of g-C3N4 / BiPO4 product and g-C3N4 / Bi / BiPO4 photocatalyst is shown in Figure 2 As shown, it can be seen that g-C3N4 / BiPO4 exhibits the morphological characteristics of nanocubes connected to flexible layered structures, while g-C3N4 / Bi / BiPO4 adds some granular structures on the basis of g-C3N4 / BiPO4.

[0103] In this example, TEM analysis of g-C3N4 / Bi / BiPO4 photocatalyst is shown in Figure 3 As shown, lattice fringes attributed to Bi can be seen, indicating the presence of reduced Bi mediators in the g-C3N4 / Bi / BiPO4 photocatalyst.

[0104] In this example, the XRD analysis of g-C3N4 / BiPO4 product and g-C3N4 / Bi / BiPO4 photocatalyst is shown in Figure 4 As shown, it can be seen that the g-C3N4 / BiPO4 product basically maintains the original crystal phase structure of BiPO4 and g-C3N4. Compared with g-C3N4 / BiPO4, the characteristic peak belonging to BiPO4 in the g-C3N4 / Bi / BiPO4 photocatalyst is weakened and a new characteristic peak appears that is consistent with Bi.

[0105] In this embodiment, the ultraviolet visible diffuse reflectance spectra (UV-vis DRS) of g-C3N4 / BiPO4 product and g-C3N4 / Bi / BiPO4 photocatalyst are shown in Figure 5 As shown, the area under the curve is the light absorption range. The visible light absorption capacity of g-C3N4 / Bi / BiPO4 is enhanced and the absorption range is expanded.

[0106] Comparative Example 2

[0107] The BiPO4 nanocubes obtained in the first step of Example 1 were placed in a muffle furnace, heated to 550°C at a rate of 5°C / min for 2 hours, and then naturally cooled to room temperature. The obtained product was recorded as annealed BiPO4 and used for subsequent photocatalytic experiments.

[0108] In this comparative example, the SEM analysis of BiPO4 after annealing is shown in Figure 2 As shown, it can be seen that it is BiPO4 in the form of nanocubes (Note: the morphology, structure and characterization results of BiPO4 that has been heat treated and that has not been heat treated do not change significantly).

[0109] In this comparative example, the XRD analysis of BiPO4 after annealing is shown in Figure 4 As shown, it can be seen that all its diffraction peaks correspond to the monoclinic BiPO4 (JCPDS#15-0767), that is, the P21 / n(14) space group, and show higher diffraction intensity at the characteristic peaks of the (120), (200) and (012) crystal planes.

[0110] In this comparative example, the ultraviolet visible diffuse reflectance spectrum (UV-vis DRS) of BiPO4 after annealing is shown in Figure 5 shown.

[0111] Comparative Example 3

[0112] The g-C3N4 / BiPO4 product obtained in the second step of Example 1 is recorded as g-C3N4 / BiPO4 and used in subsequent photocatalytic experiments.

[0113] Analysis example 1

[0114] The g-C3N4 obtained in Comparative Example 1, the BiPO4 obtained in Comparative Example 2, the g-C3N4 / BiPO4 obtained in Comparative Example 3, and the g-C3N4 / Bi / BiPO4 obtained in Example 1 were respectively used as test materials for photocatalytic experiments, and single photolysis (without catalyst) was used as a control.

[0115] The process of photocatalytic experiment is:

[0116] 10 mg of the material to be tested was added to 50 mL of tetracycline solution (tetracycline concentration was 20 mg / L, pH was 7), and it was kept in the dark for 30 min and stirred (speed 600 rpm). After reaching the adsorption-desorption equilibrium, the xenon lamp was turned on for photocatalytic reaction (visible light source, 350 W xenon lamp), and stirred during the reaction (speed 600 rpm); sampling and monitoring were performed regularly, and the reaction solution was filtered; the absorbance of the supernatant was measured by ultraviolet spectrophotometer (wavelength set to 355 nm), so as to explore the degradation performance of the catalyst.

[0117] In order to quantitatively compare the catalytic efficiency of different photocatalysts, the concentration curve of tetracycline solution was fitted kinetically. t / C0) and reaction time t are linearly related, indicating that the degradation reaction of tetracycline by the catalyst conforms to the pseudo-first-order kinetic model, and the reaction kinetic constant is calculated according to Formula 1.

[0118] ln(C t / C0) = -k·t (Formula 1)

[0119] In the formula, C0 represents the initial concentration of the reactant, C t represents the instantaneous concentration at time t, k represents the reaction kinetic constant, and t represents the reaction time (irradiation time).

[0120] In this analysis example, the experimental results are as follows Figure 6 and Figure 7 As shown in Figure 2, the degradation rate of tetracycline under photolysis alone (without catalyst) was only 1.6%, and the pseudo-first-order reaction kinetic rate was 9.76×10 -5 min -1. After adding the catalyst, the degradation rate of tetracycline was improved to varying degrees. After 90 minutes of reaction, the photocatalytic degradation rates of tetracycline by g-C3N4, BiPO4 and g-C3N4 / BiPO4 were 41.2%, 56.7% and 88.8%, respectively. The g-C3N4 / Bi / BiPO4 catalyst obtained by in-situ reduction of g-C3N4 / BiPO4 was more conducive to the decomposition of tetracycline. After 90 minutes of reaction, the photocatalytic degradation rate of tetracycline was 97.5%, and the pseudo-first-order reaction kinetic rate was 0.0400min -1 .

[0121] Analysis example 2

[0122] The g-C3N4 / Bi / BiPO4 obtained in Example 1 was used as the test material for photocatalytic experiments, and the effects of different catalyst dosages were investigated.

[0123] The specific experiments are as follows:

[0124] A preset dosage of the material to be tested was added to 50 mL of a tetracycline solution (tetracycline concentration was 20 mg / L, pH was 7), and it was kept in the dark for 30 min and stirred (speed 600 rpm). After reaching the adsorption-desorption equilibrium, the xenon lamp was turned on for illumination (visible light source, 350 W xenon lamp) to carry out a photocatalytic reaction, and the solution was stirred (speed 600 rpm) during the reaction. Samples were taken for monitoring at regular intervals, and the reaction solution was filtered. The absorbance of the supernatant was measured by an ultraviolet spectrophotometer (wavelength set to 355 nm) to explore the degradation performance of the catalyst.

[0125] In this analysis example, the preset dosage of the material to be tested is 5 mg, 10 mg, 15 mg and 20 mg respectively; see Figure 8 and Fig. 9 As shown in Figure 2, when the dosage was 5 mg, 10 mg, 15 mg and 20 mg, the degradation rates after 90 min of reaction were 86.7%, 97.5%, 99.2% and 100%, respectively, and the pseudo-first-order reaction kinetic rates were 0.0216 min -1 、0.0400min -1 、0.0504min -1 and 0.0554min -1 .

[0126] Analysis example 3

[0127] The g-C3N4 / Bi / BiPO4 obtained in Example 1 was used as the test material for photocatalytic experiments, and the effects of the initial concentrations of the four elements solutions were investigated.

[0128] The specific experiments are as follows:

[0129] 10 mg of the material to be tested was added to 50 mL of tetracycline solution (pH 7), and it was kept in the dark for 30 min and stirred (speed 600 rpm). After reaching the adsorption-desorption equilibrium, the xenon lamp was turned on for illumination (visible light source, 350 W xenon lamp) to carry out a photocatalytic reaction, and stirred during the reaction (speed 600 rpm); sampling and monitoring were performed regularly, and the reaction solution was filtered; the absorbance of the supernatant was measured by ultraviolet spectrophotometer (wavelength set to 355 nm), so as to explore the degradation performance of the catalyst.

[0130] In this analysis, the initial concentrations of tetracycline in the tetracycline solution were 10 mg / L, 20 mg / L, 30 mg / L, and 40 mg / L. Fig.10 and Fig.11 As shown in the figure, when the initial concentration of tetracycline solution is 10mg / L and 20mg / L, the degradation rate in 90min is close, which is 97.6% and 97.5% respectively; when the initial concentration of tetracycline solution is 30mg / L and 40mg / L, the degradation rate in 90min decreases, which is 89.4% and 84.8% respectively. The pseudo-first-order reaction kinetic rate corresponding to the initial concentration of tetracycline solution is 10mg / L, 20mg / L, 30mg / L and 40mg / L is 0.0485min -1 、0.0400min -1 、0.0244min -1 and 0.0206min -1 .

[0131] Analysis example 4

[0132] The g-C3N4 / Bi / BiPO4 obtained in Example 1 was used as the test material for photocatalytic experiments, and the influence of different initial pH values ​​was investigated.

[0133] The specific experiments are as follows:

[0134] 10 mg of the material to be tested was added to 50 mL of tetracycline solution (tetracycline concentration was 20 mg / L), and it was kept in the dark for 30 min and stirred (rotation speed 600 rpm). After reaching the adsorption-desorption equilibrium, the xenon lamp was turned on for illumination (visible light source, 350 W xenon lamp) to carry out a photocatalytic reaction, and stirred during the reaction (rotation speed 600 rpm); sampling and monitoring were performed regularly, and the reaction solution was filtered; the absorbance of the supernatant was measured by ultraviolet spectrophotometer (wavelength set to 355 nm), so as to explore the degradation performance of the catalyst.

[0135] In this analysis, the initial pH of the tetracycline solution was 3, 5, 7, 9, and 11, respectively; see Fig.12 and 13 As shown in the figure, under alkaline conditions, the photocatalytic degradation effect of tetracycline is significantly improved; when the pH is 11, the degradation rate of tetracycline reaches 100% within 60 minutes of reaction; the pseudo-first-order reaction kinetic rates under the conditions of pH values ​​of 3, 5, 7, 9, and 11 are 0.0220min, respectively. -1 、0.0260min -1 、0.0400min -1 、0.0764min -1 and 0.113min -1 .

[0136] Comparative Example 4

[0137] 1. Preparation of catalyst:

[0138] On the basis of Example 1, Bi(NO)3 was added during the preparation of the catalyst, and then KBH4 was added for reduction, and the obtained comparative sample was recorded as g-C3N4 / Bi / BiPO4-2.

[0139] In this comparative example, the process of synthesizing the comparative sample g-C3N4 / Bi / BiPO4-2 catalyst is as follows:

[0140] The g-C3N4 / BiPO4 product was obtained in the same manner as in the first and second steps of Example 1; 0.5 g of the g-C3N4 / BiPO4 product, 0.01 g of Bi(NO3)3·5H2O and 0.5 g of PVP (polyvinyl pyrrolidone) were added to 50 mL of deionized water, and magnetic stirring was performed for 20 min to obtain a fourth treatment liquid; a solution of potassium borohydride (50 mmol / L, 30 mL) was added dropwise to the fourth treatment liquid, and stirred for 30 min to obtain a fifth treatment liquid; the fifth treatment liquid was aged (standing at room temperature) for 30 min to obtain a sixth treatment liquid; the solid separator in the sixth treatment liquid was separated and washed with water and ethanol, and then dried at 40°C to obtain a g-C3N4 / Bi / BiPO4-2 photocatalyst for subsequent photocatalytic experiments.

[0141] 2. Photocatalytic experiment:

[0142] 10 mg of the catalyst in this comparative example was added to 50 mL of tetracycline solution (tetracycline concentration was 20 mg / L, pH was 7), and it was kept in the dark for 30 min and stirred (speed 600 rpm). After reaching the adsorption-desorption equilibrium, the xenon lamp was turned on for 90 min (visible light source, 350 W xenon lamp), and stirred during the irradiation process (speed 600 rpm). Then the reaction solution was taken out and filtered; the absorbance of the supernatant was measured by ultraviolet spectrophotometer (wavelength set to 355 nm), so as to explore the degradation performance of the catalyst.

[0143] In this comparative example, after irradiation for 90 minutes, the degradation rate of tetracycline by g-C3N4 / Bi / BiPO4-2 was 96.11%.

[0144] Comparative Example 5

[0145] 1. Preparation of catalyst:

[0146] On the basis of Example 1, an Ag precursor was added, and the obtained comparative sample was recorded as g-C3N4 / Ag / BiPO4 catalyst.

[0147] In this comparative example, the process of synthesizing the comparative sample g-C3N4 / Ag / BiPO4 catalyst is as follows:

[0148] The g-C3N4 / BiPO4 product is obtained in the same manner as in the first and second steps of Example 1; 0.5 g of the above g-C3N4 / BiPO4 product, 0.01 g of AgNO3 and 0.5 g of PVP (polyvinyl pyrrolidone) are added to 50 mL of deionized water, and magnetic stirring is performed for 20 min to obtain a fourth treatment liquid; a solution of potassium borohydride (50 mmol / L, 30 mL) is added dropwise to the fourth treatment liquid, and stirred for 30 min to obtain a fifth treatment liquid; the fifth treatment liquid is aged (standing at room temperature) for 30 min to obtain a sixth treatment liquid; the solid separator in the sixth treatment liquid is separated and washed with water and ethanol, and then dried at 40°C to obtain a g-C3N4 / Ag / BiPO4 photocatalyst for subsequent photocatalytic experiments.

[0149] 2. Photocatalytic experiment:

[0150] 10 mg of the catalyst in this comparative example was added to 50 mL of tetracycline solution (tetracycline concentration was 20 mg / L, pH was 7), and it was kept in the dark for 30 min and stirred (speed 600 rpm). After reaching the adsorption-desorption equilibrium, the xenon lamp was turned on for 90 min (visible light source, 350 W xenon lamp), and stirred during the irradiation process (speed 600 rpm). Then the reaction solution was taken out and filtered; the absorbance of the supernatant was measured by ultraviolet spectrophotometer (wavelength set to 355 nm), so as to explore the degradation performance of the catalyst.

[0151] In this comparative example, after 90 minutes of irradiation, the degradation rate of tetracycline by g-C3N4 / Ag / BiPO4 was 88.62%.

[0152] Comparative Example 6

[0153] 1. Preparation of catalyst:

[0154] On the basis of Example 1, an Au precursor was added, and the obtained comparative sample was recorded as g-C3N4 / Au / BiPO4 catalyst.

[0155] In this comparative example, the process of synthesizing the comparative sample g-C3N4 / Au / BiPO4 catalyst is as follows:

[0156] The g-C3N4 / BiPO4 product was obtained in the same manner as in the first and second steps of Example 1; 0.5 g of the g-C3N4 / BiPO4 product, 0.01 g of HAuCl4·3H2O and 0.5 g of PVP (polyvinyl pyrrolidone) were added to 50 mL of deionized water, and magnetic stirring was performed for 20 min to obtain a fourth treatment liquid; a solution of potassium borohydride (50 mmol / L, 30 mL) was added dropwise to the fourth treatment liquid, and the mixture was stirred for 30 min to obtain a fifth treatment liquid; the fifth treatment liquid was aged (standing at room temperature) for 30 min to obtain a sixth treatment liquid; the solid separator in the sixth treatment liquid was separated and washed with water and ethanol, and then dried at 40°C to obtain a g-C3N4 / Au / BiPO4 photocatalyst for subsequent photocatalytic experiments.

[0157] 2. Photocatalytic experiment:

[0158] 10 mg of the catalyst in this comparative example was added to 50 mL of tetracycline solution (tetracycline concentration was 20 mg / L, pH was 7), and it was kept in the dark for 30 min and stirred (speed 600 rpm). After reaching the adsorption-desorption equilibrium, the xenon lamp was turned on for 90 min (visible light source, 350 W xenon lamp), and stirred during the irradiation process (speed 600 rpm). Then the reaction solution was taken out and filtered; the absorbance of the supernatant was measured by ultraviolet spectrophotometer (wavelength set to 355 nm), so as to explore the degradation performance of the catalyst.

[0159] In this comparative example, after 90 minutes of irradiation, the degradation rate of tetracycline by g-C3N4 / Au / BiPO4 was 85.37%.

[0160] Comparative Example 7

[0161] 1. Preparation of catalyst:

[0162] On the basis of Example 1, BiPO4 was replaced by BiOCl, and the obtained comparative sample was recorded as g-C3N4 / Bi / BiOCl catalyst.

[0163] The preparation process of this comparative example is as follows:

[0164] The first step is the preparation of BiOCl:

[0165] 1mmol Bi(NO3)3·5H2O and 1mmol NaCl were ultrasonically stirred in 40mL ethylene glycol to form a first treatment liquid, which was transferred to a 100mL polytetrafluoroethylene-lined high-pressure reactor; the reactor was placed in an electric constant temperature forced air drying oven and reacted at 160°C for 12h to obtain a reaction liquid; the solid separator in the reaction liquid was separated and washed several times with ethanol and high-purity water; then, the solid separator was dried in a 70°C oven for 10h to obtain a BiOCl material.

[0166] Step 2: Preparation of g-C3N4 / BiOCl composite catalyst:

[0167] Add 3 g of melamine and 150 mg of the above-mentioned BiOCl material to 20 mL of ethanol (analytical grade, 99.5%), stir and disperse evenly by ultrasound to obtain a second treatment liquid; put the second treatment liquid into a crucible, and dry it in an oven at 80°C for 6 h to obtain a dried product; put the dried product into a muffle furnace, heat it to 550°C at a rate of 5°C / min, thermally polymerize it for 2 h, and then naturally cool it to room temperature. The obtained product is recorded as g-C3N4 / BiOCl product.

[0168] The third step is to synthesize the comparative sample g-C3N4 / Bi / BiOCl catalyst:

[0169] 0.5 g of the above g-C3N4 / BiOCl product and 0.5 g of PVP (polyvinyl pyrrolidone) were added to 50 mL of deionized water, and magnetic stirring was carried out for 20 min to obtain a third treatment liquid; a solution of potassium borohydride (50 mmol / L, 30 mL) was added dropwise to the third treatment liquid, stirred for 30 min, to obtain a fourth treatment liquid; the fourth treatment liquid was aged (standing at room temperature) for 30 min to obtain a fifth treatment liquid; the solid separator in the fifth treatment liquid was separated and washed with water and ethanol, and then dried at 40°C to obtain a g-C3N4 / Bi / BiOCl photocatalyst for subsequent photocatalytic experiments.

[0170] 2. Photocatalytic experiment:

[0171] 10 mg of the catalyst in this comparative example was added to 50 mL of tetracycline solution (tetracycline concentration was 20 mg / L, pH was 7), and it was kept in the dark for 30 min and stirred (speed 600 rpm). After reaching the adsorption-desorption equilibrium, the xenon lamp was turned on for 90 min (visible light source, 350 W xenon lamp), and stirred during the irradiation process (speed 600 rpm). Then the reaction solution was taken out and filtered; the absorbance of the supernatant was measured by ultraviolet spectrophotometer (wavelength set to 355 nm), so as to explore the degradation performance of the catalyst.

[0172] In this comparative example, after 90 minutes of irradiation, the degradation rate of tetracycline by g-C3N4 / Bi / BiOCl was 82.16%.

[0173] Comparative Example 8

[0174] 1. Preparation of catalyst:

[0175] On the basis of Example 1, BiPO4 was replaced by BiOI, and the obtained comparative sample was recorded as g-C3N4 / Bi / BiOI catalyst.

[0176] The preparation process of this comparative example is as follows:

[0177] The first step is the preparation of BiOI:

[0178] 1mmol Bi(NO3)3·5H2O and 1mmol KI were ultrasonically stirred in 40mL ethylene glycol to form a first treatment liquid, which was transferred to a 100mL polytetrafluoroethylene-lined autoclave. The autoclave was placed in an electric constant temperature blast drying oven and reacted at 160°C for 12h to obtain a reaction liquid; the solid separation in the reaction liquid was separated and washed several times with ethanol and high-purity water; then, the solid separation was dried in a 70°C oven for 10h to obtain a BiOI material.

[0179] Step 2: Preparation of g-C3N4 / BiOI composite catalyst:

[0180] 3 g of melamine and 150 mg of the above-mentioned BiOI material were added to 20 mL of ethanol (analytical grade, 99.5%), stirred and ultrasonically dispersed uniformly to obtain a second treatment liquid; the second treatment liquid was placed in a crucible and dried in an oven at 80°C for 6 h to obtain a dried product; the dried product was placed in a muffle furnace, heated to 550°C at a rate of 5°C / min, thermally polymerized for 2 h, and then naturally cooled to room temperature. The obtained product was recorded as g-C3N4 / BiOI product.

[0181] The third step is to synthesize the comparative sample g-C3N4 / Bi / BiOI catalyst:

[0182] 0.5 g of the above g-C3N4 / BiOI product and 0.5 g of PVP (polyvinyl pyrrolidone) were added to 50 mL of deionized water, and magnetic stirring was performed for 20 min to obtain a third treatment liquid; a solution of potassium borohydride (50 mmol / L, 30 mL) was added dropwise to the third treatment liquid, stirred for 30 min, to obtain a fourth treatment liquid; the fourth treatment liquid was aged (standing at room temperature) for 30 min to obtain a fifth treatment liquid; the solid separator in the fifth treatment liquid was separated and washed with water and ethanol, and then dried at 40°C to obtain a g-C3N4 / Bi / BiOI photocatalyst for subsequent photocatalytic experiments.

[0183] 2. Photocatalytic experiment:

[0184] 10 mg of the catalyst in this comparative example was added to 50 mL of tetracycline solution (tetracycline concentration was 20 mg / L, pH was 7), and it was kept in the dark for 30 min and stirred (speed 600 rpm). After reaching the adsorption-desorption equilibrium, the xenon lamp was turned on for 90 min (visible light source, 350 W xenon lamp), and stirred during the irradiation process (speed 600 rpm). Then the reaction solution was taken out and filtered; the absorbance of the supernatant was measured by ultraviolet spectrophotometer (wavelength set to 355 nm), so as to explore the degradation performance of the catalyst.

[0185] In this comparative example, after 90 minutes of irradiation, the degradation rate of tetracycline by g-C3N4 / Bi / BiOI was 89.77%.

[0186] The above technical solutions of the present invention are only preferred embodiments of the present invention, and the patent scope of the present invention is not limited thereto. All equivalent structural changes made by using the contents of the present invention specification and drawings under the technical concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.

Claims

1. A method for preparing a g-C3N4 / Bi / BiPO4 photocatalyst, characterized in that: Includes steps: S1, obtain BiPO4 nanocubes; S2, obtaining a g-C3N4 / BiPO4 product based on the BiPO4 nanocubes; S3, obtaining a g-C3N4 / Bi / BiPO4 photocatalyst based on the g-C3N4 / BiPO4 product; The process of obtaining the g-C3N4 / Bi / BiPO4 photocatalyst based on the g-C3N4 / BiPO4 product comprises the following sub-steps: S31, mixing polyvinyl pyrrolidone and the g-C3N4 / BiPO4 product in water to obtain a fourth treatment liquid; the mass ratio of the polyvinyl pyrrolidone to the g-C3N4 / BiPO4 product is 0.8-1.2:0.8-1.2; S32, adding a potassium borohydride solution dropwise to the fourth treatment liquid and mixing the mixture to obtain a fifth treatment liquid; the mass volume ratio of the g-C3N4 / BiPO4 product to the potassium borohydride solution is 1 g: 50-70 mL, and the concentration of the potassium borohydride solution is 30-70 mmol / L; S33, aging the fifth treatment liquid to obtain a sixth treatment liquid; S34, performing solid-liquid separation on the sixth treated liquid to obtain the g-C3N4 / Bi / BiPO4 photocatalyst.

2. The method for preparing the g-C3N4 / Bi / BiPO4 photocatalyst according to claim 1, characterized in that: The process of obtaining the BiPO4 nanocubes includes the following sub-steps: S11, mixing ethylenediaminetetraacetic acid and bismuth nitrate in water, and adding nitric acid during the mixing process to obtain a first treatment solution; the molar ratio of the ethylenediaminetetraacetic acid to the bismuth nitrate is 0.8-1.2:0.8-1.2; the amount of the nitric acid added is based on the transparency of the solution; S12, mixing the first treatment liquid and dipotassium hydrogen phosphate to obtain a second treatment liquid; the molar ratio of the dipotassium hydrogen phosphate to the bismuth nitrate is 0.8-1.2:0.8-1.2; S13, subjecting the second treatment liquid to a hydrothermal treatment to obtain a reaction liquid; the temperature of the hydrothermal treatment is 160-200° C., and the duration of the hydrothermal treatment is 8-15 hours; S14, performing solid-liquid separation on the reaction solution to obtain BiPO4 nanocubes.

3. The method for preparing the g-C3N4 / Bi / BiPO4 photocatalyst according to claim 2, characterized in that: In the sub-step S11, the ratio of bismuth nitrate to water is 5 mmol: 50-100 mL; In the sub-step S14, during the solid-liquid separation, the solid separation is washed, and after the solid-liquid separation, the solid separation is dried at 60-80° C. for 8-15 hours.

4. The method for preparing the g-C3N4 / Bi / BiPO4 photocatalyst according to claim 1, characterized in that: The process of obtaining the g-C3N4 / BiPO4 product based on the BiPO4 nanocubes comprises the following sub-steps: S21, mixing melamine and the BiPO4 nanocubes in ethanol to obtain a third treatment liquid; the mass ratio of the melamine to the BiPO4 nanocubes is 10-30:1; S22, drying the third treatment liquid to obtain a dried product; S23, subjecting the dried material to thermal polymerization treatment, and obtaining the g-C3N4 / BiPO4 product after cooling; the temperature of the thermal polymerization treatment is 500-600°C, and the insulation time of the thermal polymerization treatment is 1.5-3h.

5. The method for preparing the g-C3N4 / Bi / BiPO4 photocatalyst according to claim 4, characterized in that: In the sub-step S21, the mass volume ratio of the melamine to the ethanol is 1-5 g:20 mL; In the sub-step S22, the temperature of the drying process is 70-90°C, and the duration of the drying process is 5-8h; In the sub-step S23, the heating rate during the thermal polymerization treatment is 3-10°C / min.

6. The method for preparing the g-C3N4 / Bi / BiPO4 photocatalyst according to claim 1, characterized in that: In the sub-step S31, the mass volume ratio of the g-C3N4 / BiPO4 product and water is 0.1-1g:50mL.

7. The method for preparing the g-C3N4 / Bi / BiPO4 photocatalyst according to claim 1, characterized in that: In the sub-step S32, mixing is performed during the process of adding the potassium borohydride solution dropwise to the fourth treatment liquid, and the mixing is continued for 20-40 minutes after the completion of the dropping; In the sub-step S33, the aging time is 20-40 minutes. In the sub-step S34, during the solid-liquid separation, the solid separated product is washed, and after the solid-liquid separation, the solid separated product is dried at 30-50°C.

8. A g-C3N4 / Bi / BiPO4 photocatalyst, characterized in that: The preparation is carried out by the preparation method according to any one of claims 1 to 7.

9. Use of the g-C3N4 / Bi / BiPO4 photocatalyst as claimed in claim 8 in photocatalytic degradation of organic pollutants.

10. The use according to claim 9, characterized in that: The organic pollutants include tetracycline.